Optimization and Application Effect Evaluation of Cloud Data Integrity Verification Algorithm for Accounting Informatization - Guo, Yao (International journal of grid and high performance computing, 2025)
With the development of information technology, accounting big data plays an increasingly important role in supporting enterprise decision-making. Aiming to address problems of data security and privacy protection in the existing cloud data storage environment, this article proposes a data integrity verification algorithm based on bilinear pairing and hash functions. By analyzing the characteristics and task processing flow of modern accounting information systems and reviewing current research, an efficient and safe data integrity verification scheme is designed and implemented. This scheme not only verifies the integrity of data indefinitely but also reduces the consumption of resources. The experimental results show that, compared with traditional file transfer protocols and provable data possessions, the new method reduces the communication overhead and has higher verification efficiency when dealing with large files. The research in this article provides new ideas and technical means for improving the security of accounting information systems and has important practical application value.